Analisis Sejarah Kebijakan dan Muatan Isi PAI pada KI-KD Kurikulum 2013 dan CP Kurikulum Merdeka - Hatim Gazali; M. Munir (Indonesian Journal of Islamic Religious Education, 2025)
This article explores the evolution of Islamic Religious Education (PAI) policy in Indonesia, tracing its development from the colonial era to the present day. It also examines how PAI content is represented in the Core Competencies and Basic Competencies (KI-KD) of the 2013 Curriculum and in the Learning Outcomes (CP) of the Merdeka Curriculum. The study adopts a qualitative approach, utilizing historical analysis and content analysis to investigate both policy developments and curriculum content related to PAI. The findings reveal that state policies on PAI have been dynamic, closely tied to the broader political landscape of Islam in Indonesia. These range from the prohibition of PAI in schools during the colonial period, to the official recognition of Islamic education institutions such as madrasahs during the New Order era, and finally to the acknowledgment of pesantren (Islamic boarding schools) during the Reformasi period. In terms of content, PAI in the 2013 Curriculum (KI-KD) includes a wide range of competencies. However, inconsistencies were found between the graduation standards (SKL), content standards (SI), and the core/basic competencies themselves. In contrast, the PAI component of the Merdeka Curriculum demonstrates more coherent learning progressions across phases and outlines competencies that are more integrated and conceptually advanced.